Origin and Health Status of First-Generation Africans from Early Colonial Mexico - (:unkn) unknown (My University, 2020)
Highlights d Genomic and isotopes data suggest an African origin for the three individuals d One 14X Treponema pallidum sub. pertenue genome was recovered d One 1,500X hepatitis B virus genome was recovered d Both pathogen genomes cluster together with present day pathogens from Africa Authors
Keywords: African Research